Circular Training in The Development of Physical Qualities of Those Involved in Physical Education Features Of Using the Style - Fatxulla Miraxmedov (Euro Asian Journal Publishing, 2024)
The article describes in detail the effective use of circuit training techniques in the development of physical abilities and qualities in physical education lessons
Keywords: physical adjectives; circuit training; school age; physical education